Pelatihan Tour Planner Pengelola Desa Wisata YTR Ohoi Letman sebagai Upaya Pengembangan Paket Wisata Terintegrasi - Betaubun, Kamilius D.; Abdullah, Rahmat (Bakti Budaya: Jurnal Pengabdian kepada masyarakat, 2024)
Along with the current development of tourist villages , the YTR Ohoi Letman tourist village should have tour planners that are able to integrate its tourist attractions and tourist facilities into tour packages. Nowadays in actual fact, this tourist village has not had a tour planner. For this reason, we took initiative to conduct education and training to share the knowledge and skills about how to become a tour planner for the members of POKDARWIS. Lectures are used as an education method using the Contextul Teaching and Learning model, where the material explained is related to the current situation in the travel industries. And for training sesson, is used method of Small Group Discussion where the presenter makes a task plan, then discussed by the participants and presented at the same time. In general, the education and training has run succesfully where the members of POKDARWIS seemed very enthusiastic and interactive and they were able to plan, calculate and arrange the tour packages. There are two ready made tour packages are produced during the event, they are YTR Ohoi Letman Exotic Tours 3Days/2Nights and YTR Ohoi Letman Explore Nature Tourism 3 Days 2 Nights. === Sebagai desa wisata berkembang, desa wisata YTR Ohoi Letman seharusnya memiliki tour planner yang mampu mengintegrasikan atraksi dan fasilitas wisata yang dimiliki dalam bentuk paket wisata. Faktanya, sampai saat ini, desa wisata tersebut belum memiliki tour planner. Untuk itu, kami berinisiatif untuk melakukan penyuluhan dan pelatihan guna membentuk pengetahuan dan keterampilan para POKDARWIS untuk menjadi tour planner. Ceramah dipakai sebagai metode penyuluhan dengan model Contextul Teaching and Learning. Materi yang dijelaskan dikaitkan dengan situasi industri perjalanan wisata, sedangkan dalam pelatihan, metode yang dipakai ialah Small Group Discussion. Pemateri membuat rancangan tugas dan didiskusikan oleh peserta sekaligus dipresentasikan. Secara umum, penyuluhan dan pelatihan berjalan lancar. Para POKDARWIS terlihat sangat antusias dan interaktif serta mampu merencanakan, menghitung, dan meyusun paket wisata. Terdapat 2 paket wisata ready made tour yang dihasilkan, yaitu YTR Eksotik Tours dan Explore Wisata Alam YTR Ohoi Letman 3 Hari 2 Malam.